Mediterranean Identities Environment, Society, Culture - Fuerst-Bjelis, Borna (IntechOpen, 2017)
What is the Mediterranean? The perception of the Mediterranean leans equally on the nature, culture, history, lifestyle, and landscape. To approach the question of identity, it seems that we have to give importance to all of these. There is no Mediterranean identity, but Mediterranean identities. Mediterranean is not about the homogeneity and uniformity, but about the unity that comes from diversities, contacts, and interconnections. The book tends to embrace the environment, society, and culture of the Mediterranean in their multiple and unique interconnections over the millennia, contributing to the better understanding of the essential human-environmental interrelations. The choice of 17 chapters of the book, written by a number of prominent scholars, clearly shows the necessity of the interdisciplinary approach to the Mediterranean identity issues. The book stresses the most serious concerns of the Mediterranean today - threats to biodiversity, risks, and hazards - mostly the increasing wildfires and finally depletion of traditional Mediterranean practices and landscapes, as constituent parts of the Mediterranean heritage.